The territory of Japan its history and legal basis - Serita, Kentaro (Japan library., 2018)
"The Northern Territories, Takeshima, and the Senkaku Islands--what exactly is the territorial extent of Japan? To answer this fundamental question, the author, an authority on international law, retraces and analyzes the history of negotiations over these territories, while also setting forth his vision of the future of issues concerning territorial land, air, and sea"--Dust jacket.